An heuristic algorithm for fair strategic personnel assignment in continuous operation. (15th October 2020) - Immonen, Eero; Putkonen, Ari
This article introduces an heuristic initialise-and-refine algorithm for fair strategic (long-term) personnel assignment in continuous operation. Here, continuous operation refers to stable, reoccurring parallel work processes, with known tasks and constant demand - an example of which is given by university tuition on a degree program across many years. The proposed method attempts to address both the employees' competency-preference matching and the workload balancing aspects of fairness simultaneously, in situations where the task schedule across the parallel production lines is known beforehand. As an application, the proposed method is successfully used for optimising the module assignment of teachers in a Mechanical Engineering degree program at a Finnish university.